1993
DOI: 10.1002/ijc.2910540116
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of platelet eicosanoid metabolism and integrin αIIbβ3 in tumor‐cell‐induced platelet aggregation

Abstract: Platelet eicosanoid metabolism resulting from tumor-cell-induced platelet aggregation (TCIPA) was examined in a homologous in vitro system. Rat Walker 256 carcinosarcoma cells induced the aggregation of rat platelets via a thrombin-dependent mechanism with concomitant production of eicosanoid metabolites (e.g., 12-HETE, TXA2). TCIPA was dependent on the concentration of tumor cells inducing aggregation, as well as cyclooxygenase and lipoxygenase products. Cyclooxygenase inhibitors, but not lipoxygenase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 22 publications
(26 reference statements)
0
39
0
Order By: Relevance
“…We suspect that this is possible since the physiological levels of 12(S)-HETE (0.1-1.0 µM) have been shown to mimic the thrombin effect on platelet ␣IIb␤3 expression (Steinert et al, 1993) which has been correlated with tumor-cell adhesion to endothelial cells and cancer metastasis (Honn and Tang, 1992). Furthermore, our preliminary studies have shown that both nordihydroguaiaretic acid (a general LOX inhibitor) and N-benzyl-B-hydroxy-5-phenylpentanamide (12-LOX inhibitor) induce B16a cell death, which results in a subsequent appearance of non-specific cleavage of actin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that this is possible since the physiological levels of 12(S)-HETE (0.1-1.0 µM) have been shown to mimic the thrombin effect on platelet ␣IIb␤3 expression (Steinert et al, 1993) which has been correlated with tumor-cell adhesion to endothelial cells and cancer metastasis (Honn and Tang, 1992). Furthermore, our preliminary studies have shown that both nordihydroguaiaretic acid (a general LOX inhibitor) and N-benzyl-B-hydroxy-5-phenylpentanamide (12-LOX inhibitor) induce B16a cell death, which results in a subsequent appearance of non-specific cleavage of actin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Morphologic observations show tumor cells closely associated with platelets after vascular arrest (10,11). A variety of platelet factors contribute to this binding including the glycoproteins, integrin ␣ IIb ␤ 3 (12)(13)(14). P-selectin has also been shown to facilitate metastasis of tumor cells bearing P-selectin ligand (15).…”
Section: Introductionmentioning
confidence: 99%
“…Systematic studies correlating the in vitro and in vivo interactions of cancer cells with platelets have provided the most comprehensive picture to date of this complex process [1, 7, 12, 13] (fig. 1; table 1).…”
Section: Mechanism Of the Early Phase Of Hematogenous Dissemination Omentioning
confidence: 99%
“…Studies on the molecular mechanisms of the interaction of cancer cells with platelets revealed that the earliest player in this interaction is P-selectin in platelets and P-selectin glycoprotein ligand-1/CD162, heparan sulfate proteoglycan (HSPG) and sialyl-Lewis A/X in cancer cells, corresponding to the rolling/docking phases [20, 21] (table 1). The subsequent phase of the interaction of cancer cells with platelets involves β3 integrin-mediated processes (where thrombospondin and fibrinogen can serve as molecular bridges) [12, 13], while the later phase is characterized by activation of both partners involving the prothrombogenic proteins such as tissue factor (TF), cancer procoagulant [2, 5] or HLA-DR [22]. Revealing the molecular background of the activation phase of both tumor cells and platelets, the involvement of the lipid-signaling pathway was demonstrated [13].…”
Section: Mechanism Of the Early Phase Of Hematogenous Dissemination Omentioning
confidence: 99%
See 1 more Smart Citation